Tanggung Jawab Hukum Bank Digital terhadap Perlindungan Konsumen di Indonesia - Kurniawan, Dimas Amal; Aliyah, Rahma; Rizqi, Aditya Maulana (JATIJAJAR LAW REVIEW, 2024)
he development of digital banking in Indonesia presents various legal challenges related to consumer protection. Although digital innovation provides easy access to financial services, there are still weaknesses in legal protection for consumers due to the lack of regulations that allow for the complexity of digital banking transactions. This study aims to analyze the legal responsibility of digital banks in protecting consumers and review the suitability of applicable regulations with the needs of consumer protection in the digital era. The research method used is normative legal research with a regulatory-statutory approach (statutory approach) and a contextual approach (conceptual approach). Data were obtained through a literature review of regulations, court decisions, and relevant academic literature. The results of the study show that banking regulations in Indonesia still do not fully anticipate the risks of digital transactions, so it is necessary to strengthen regulations in terms of information transparency, data security, and settlement mechanisms for consumers. This study contributes to the development of legal policies that are more adaptive to the development of digital banking and increasing legal protection for consumers in Indonesia.